Acute Appendicitis Seen at Analankininina University Hospital during the Covid-19 Pandemic - Razafindraibe VB; Jonatana AD; Rahantasoa FCFP; Samison LH; Rakotoarijaona AH (Journal La Medihealtico, 2020)
Acute appendicitis was often diagnosed at the complication stage during the Covid19 pandemic at CHU Analankininina Toamasina. Our objective was to discuss the particularity of the management of appendicitis during the pandemic. Our study was prospective, descriptive for 6 months and took place in the general surgery department of the Analankininina Toamasina University Hospital Center, Madagascar from March 2020 to August 2020. We had collected 28 patients. The sex ratio was 3.66. The average age was 27.57 years. Appendicular abscess represented 64.29% (n=18) of the appendicular patients operated in emergency. Appendicular plastron occupied 14.29% (n=2) and generalized acute peritonitis was 7.14% (n=2). Post-operative follow-up was simple in 71.43% (n=20). The average length of hospitalization was 4 days. Acute appendicitis is often complicated during the Covid 19 pandemic in our hospital center. Surgery was systematic in our hospital, contrary to some literature which advocated antibiotic therapy at an early stage in front of the health emergency.